2017
DOI: 10.1186/s40545-017-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Taking the lead from our colleagues in medical education: the use of images of the in-vivo setting in teaching concepts of pharmaceutical science

Abstract: Despite pharmaceutical sciences being a core component of pharmacy curricula, few published studies have focussed on innovative methodologies to teach the content. This commentary identifies imaging techniques which can visualise oral dosage forms in-vivo and observe formulation disintegration in order to achieve a better understanding of in-vivo performance. Images formed through these techniques can provide students with a deeper appreciation of the fate of oral formulations in the body compared to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…New and maturing technologies enable traditional principles of pharmaceutical science to be visualized (Curley et al, 2017a ). Whilst there has been some literature to describe the perspectives of visual teaching on pharmaceutical science learning (Fox et al, 2007 ; Yellepeddi and Roberson, 2016 ), limited research is available surrounding effective teaching strategies in pharmaceutical science education and its wide application within pharmacy practice and pharmacy curricula to date (Curley et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New and maturing technologies enable traditional principles of pharmaceutical science to be visualized (Curley et al, 2017a ). Whilst there has been some literature to describe the perspectives of visual teaching on pharmaceutical science learning (Fox et al, 2007 ; Yellepeddi and Roberson, 2016 ), limited research is available surrounding effective teaching strategies in pharmaceutical science education and its wide application within pharmacy practice and pharmacy curricula to date (Curley et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work (Curley et al, 2017a ), we have demonstrated the ability to acquire in-vivo images of the disintegration of different formulations of paracetamol and have compared them with standard bench-top experiments. We proposed that images, such as these, could be used in the teaching of pharmaceutical sciences to allow for the application of concepts in a patient-centered manner (Curley et al, 2017b ). The research in this publication concentrates on evaluating the impact of integrating novel visual aids in the teaching of disintegration principles and associated formulations.…”
Section: Introductionmentioning
confidence: 99%